Leading for All: Embracing Diversity, Equity, and Inclusion in Educational Leadership - Assefa, Dr. Easaw Alemayehu (The Journal of Quality in Education, 2025)
This paper aims to address the increasing diversity in educational settings, with a focus on the necessity for educational leaders to adopt Diversity, Equity, and Inclusion (DEI) principles as global student enrollment hits approximately 1.5 billion. Utilizing a scoping review methodology, the study investigates critical components of DEI, including equitable access to resources, inclusive curricula, culturally responsive teaching, community engagement, and technology integration. The manuscript identifies best practices and strategic approaches for effectively implementing DEI initiatives. Key findings highlight the importance of ongoing professional development for educators to foster culturally competent teaching practices and to involve marginalized communities in decision-making processes. It advocates for educational leaders to prioritize DEI as a foundational element of their mission. By fostering inclusive environments, leaders can empower all students and enhance educational outcomes, which not only supports academic achievement but also contributes to broader social justice goals. It underscores the moral imperative for leaders to dismantle systemic inequities that hinder the success of marginalized students, ultimately shaping a more equitable future for society through committed DEI efforts.